Crop rotation and agri‐environment schemes determine bumblebee communities via flower resources. Issue 4 (28th February 2018) - Marja, Riho; Viik, Eneli; Mänd, Marika; Phillips, James; Klein, Alexandra‐Maria; Batáry, Péter
Abstract: In many parts of the world, farmland pollinators decreased significantly during the last half of the 20th century mainly due to land‐use changes and agricultural intensification. We studied the effect of different typical crop rotations and agri‐environment schemes (AES) on bumblebee diversity in Estonia. We compared species abundances between four crop rotation types (cereal rollover [no change from 1 year to the next], cereal to mass‐flowering crops [hereafter MFC], MFC rollover and MFC to cereal fields) where all counts were conducted in the second year and in three farming types (conventional farming, organic farming and environmentally friendly management). We surveyed bumblebees and flower cover along 401 field margins in five consecutive years and recorded 20 species and more than 6, 000 individuals. Abundances of long‐tongued and threatened bumblebee species were higher at the field margins of cereal rollover fields than for the other three crop rotation types. In addition, cereal rollover field margins had higher abundances of medium colony species, generalists and forest‐scrub species than MFC rollover and MFC to cereal or cereal to MFC field margins. Bumblebee species richness was higher at the field margins of both AES types than those of conventional farming. However, in general, the strongest driver of bumblebee presence was flower cover. Higher bumblebee abundances in cereal rollover field margins were probably owing to a concentration effect there and/or a dilution effect into MFC fields. Both AES schemes supported increasing flower cover in field margins and thereby diversity of bumblebees, indicating positive AES impacts upon wild pollinators. Synthesis and applications . Crop rotation and agri‐environment schemes determine bumblebee richness and abundance via the availability of flower resources, but crop rotation constrains bumblebees differently based on their traits. Therefore, future agri‐environmental policy should account for these management options. Crop rotation could be a simple, but efficient solution to increase the biodiversity of agricultural landscapes. Abstract : Crop rotation and agri‐environment schemes determine bumblebee richness and abundance via the availability of flower resources, but crop rotation constrains bumblebees differently based on their traits. Therefore, future agri‐environmental policy should account for these management options. Crop rotation could be a simple, but efficient solution to increase the biodiversity of agricultural landscapes.